Diversity of fish caught in Pangkalan Susu’s Marine, Langkat District, North Sumatera Province - Syahriani Hasibuan Julia; Enggar Susetya Ipanna; Fauzia Dewinta Astrid; Mellyginta Sinuhaji Simpati; Handayani Fitri (BIO Web of Conferences)
Pangkalan Susu is the second largest contributor of fishermen from nine sub-districts in Langkat Regency. The diversity of fish in Pangkalan Susu illustrates the wealth of fish in sea obtained from fishing efforts carried out by fishermen at the high demand of the community. This study aims to analyze the diversity of fish species caught in the Pangkalan Susu Sea, Langkat Regency. This study was conducted for 4 month with a sampling interval of one month once in June - August 2024 using the random purposive sampling method in Pangkalan Susu’s sea. Data analysis used in this study is relative abundance (KR), Shannon-Wienner index (H'), uniformity index (E), and dominance index (C). The total fish catch during the study period was 697 individuals, which were divided into 52 fish species and 30 families. The number of catches in consisting of 30 families and 52 species. In June, 144 fish consisting of 25 species were obtained, in July 330 fish consisting of 25 species, and in August 223 fish consisting of 21 species. The value of the fish species diversity index in Pangkalan Susu sea is included in the moderate category the diversity index value in June was 1.011, July was 0.966 and August was 0.886. The small population uniformity and dominance index values show that fish species were evenly distributed during the study with no dominant species.